2018
DOI: 10.3389/fphar.2018.00084
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Combined Gemcitabine and Birinapant in Pancreatic Cancer Cells

Abstract: Pancreatic cancer is characterized by mutated signaling pathways and a high incidence of drug resistance. Comprehensive, large-scale proteomic analysis can provide a system-wide view of signaling networks, assist in understanding drug mechanisms of action and interactions, and serve as a useful tool for pancreatic cancer research. In this study, liquid chromatography-mass spectrometry-based proteomic analysis was applied to characterize the combination of gemcitabine and birinapant in pancreatic cancer cells, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 62 publications
0
38
0
Order By: Relevance
“…Moreover, the PI3K/AKT pathway that was recently shown to be downregulated by nitroxoline www.nature.com/scientificreports www.nature.com/scientificreports/ in prostate cancer cells 12 emerged as one of the Canonical Pathways highly enriched by IPA in our proteomic analysis. Intriguingly, sirtuin and mTOR were previously reported to be upregulated in gemcitabine-resistant PC cells 35 . In addition, inhibition of PI3K, an enzyme downregulated by nitroxoline in our study, was previously shown to sensitize to gemcitabine 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the PI3K/AKT pathway that was recently shown to be downregulated by nitroxoline www.nature.com/scientificreports www.nature.com/scientificreports/ in prostate cancer cells 12 emerged as one of the Canonical Pathways highly enriched by IPA in our proteomic analysis. Intriguingly, sirtuin and mTOR were previously reported to be upregulated in gemcitabine-resistant PC cells 35 . In addition, inhibition of PI3K, an enzyme downregulated by nitroxoline in our study, was previously shown to sensitize to gemcitabine 36 .…”
Section: Discussionmentioning
confidence: 99%
“…8 Liquid chromatographymass spectrometry (LC-MS) analysis of total extracted proteins used a nano-flow liquid chromatography (LC; Eksigent, Dublin, CA), an Orbitrap Fusion mass spectrometry (MS) analyzer (ThermoFisher, Waltham, MA), and the Ionstar workflow to provide accurate, sensitive, and highthroughput identification and quantification of proteins, as described previously. [9][10][11][12][13] Analysis of the same protein samples by Western blotting provided supporting information and validation. Figure 1 shows a schematic of the QSP model.…”
Section: Cell Culture and Cell-based Experimentsmentioning
confidence: 99%
“…Our proteomic analysis identified and quantified 1,481 proteins that were changed significantly by gemcitabine and birinapant. 9 Together with published literature, they provide data for key signaling pathways relevant to drug mechanisms of action and interactions. Mechanistic information for pathways regulating cell cycle progression, DNA damage response (DDR), DNA repair, mitogen-activated protein kinase (MAPK)-p38, nuclear factor-kappa β (NFκβ), and intrinsic and extrinsic apoptosis was summarized to support the development of the system network model ( Figure 1).…”
Section: Mechanisms Of Drug Action and Interactions That Support The mentioning
confidence: 99%
See 2 more Smart Citations